2022
DOI: 10.1111/jonm.13539
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between organisational silence and organisational learning in nurses: A cross‐sectional study

Abstract: Aims: To assess the organisational silence and learning levels among nurses of a university hospital and explore the relationship between the socio-demographics, organisational silence and learning.Background: Organisational learning is an active process needed for improving organisational performance, and silence has a devastating impact on an organisation's capacity to learn.Methods: A cross-sectional quantitative design was applied using two tools: the organisational silence and the organisational learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…This finding was consistent with the findings of a research done at Jordanian capital health settings, which found that staff experience a moderate to high level of perceived general organizational silence [ 40 ]. Another survey done in the same university hospital in Egypt [ 33 ] found that the average perceived overall organizational silence level is moderate. The most unexpected conclusion in the current study was that nurses exhibit excellent levels of performance while working in a hazardous atmosphere and practicing silence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was consistent with the findings of a research done at Jordanian capital health settings, which found that staff experience a moderate to high level of perceived general organizational silence [ 40 ]. Another survey done in the same university hospital in Egypt [ 33 ] found that the average perceived overall organizational silence level is moderate. The most unexpected conclusion in the current study was that nurses exhibit excellent levels of performance while working in a hazardous atmosphere and practicing silence.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study, regulatory reasons, anxiety about destroying relationships with coworkers, fear of fines, fear of being isolated, lack of management support, and fear of being ignored are all factors that contribute to nurses’ silence [ 30 32 ]. Previous research has found that nurses with more nursing and employment experience, as well as those who are older, have higher levels of quietness [ 33 ]. Organizational elements that encourage nurses to remain silent include an unfair culture, a lack of psychological safety, a quiet climate, a hierarchical structure, a negative leadership style and lack of confidence in supervisors, and a hostile nursing work environment [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the voice behavior of nurses is imperative, especially in countries with a bulky nursing workforce as Egypt (20) . Nurse managers and leaders can create a work atmosphere that encourages and promotes open communication among nurses and other health care team members, likewise, creating an environment conducive to translating experiences into organizational learning of promoting voice behaviors (21) .…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The scoring system for the part of confidence was classified into: low confidence level (24-56), moderate confidence level (57-88) and high confidence level (89-120). The scoring system for the part of job satisfaction was classified into: low level of job satisfaction (9-21), moderate level of job satisfaction (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and high level of job satisfaction (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Total score for the three section of tool II were summed-up and the total was divided by the number of the items, giving a percent score.…”
Section: Scoring Systemmentioning
confidence: 99%
“…Likewise, creating an environment conducive to translating experiences into organizational learning and promoting competent role transition. (27) Aim of the study The aim of this study was to determine the effect of transitional training program on knowledge and experience of novice nurses' role transition experience in critical care units at Alexandria Main University Hospital. Research hypotheses H1: Nurses' knowledge is significantly and positively improved after attending a role transition training program in critical care units at Alexandria Main University Hospital.…”
Section: Introductionmentioning
confidence: 99%